Responsible Commercial Activity Of Smes And Specific Values Of Sustainable Development In Terms Of The European Excellence Model - Marieta Olaru; Vasile Dinu; Ghiorghiţa Stoleriu; Diana Şandru; Violeta Dincă (Amfiteatru Economic Journal, 2010)
The paper underlines part of the value of the research based on survey results conducted on SMEs in Romania, in 2007-2008, within the national research project IDEAS 856 "Increasing the competitiveness of SMEs in Romania by implementing a model evaluation and improvement of their performance in accordance with the European model of quality management.” One of the research objectives was the assessment of the satisfaction degree of requirements relating to protection of human health and environmental protection by SMEs from Romania, including those in trade, in terms of an integrated approach to sustainable development values within the European Excellence Model as defined by the European Foundation for Quality Management - EFQM). As a consequence of the study it appears that there is a correlation between the degree of meeting these requirements and mature quality management system of enterprises. Thus, it was found that for SMEs in trade, whose interests in implementing a quality management system is in its early stages, the degree of satisfaction of the requirements of society, from the perspective of an integrated approach to sustainable development values in the EFQM Excellence Model, is relatively low. On the other hand, research carried out showed that data obtained by SMEs in trade in the process of evaluating and monitoring the impact on the environment are used mainly to establish corrective actions, following the complaints occurred, and less to define continuous improvement programs to meet these requirements.
Keywords: M10; 330; responsible commercial activity; sustainable development; demands of society; social responsibility; SMEs in trade; the EFQM excellence model